Media guidelines for the responsible reporting and depicting of non-suicidal self-injury. (August 2021) - Westers, Nicholas J.; Lewis, Stephen P.; Whitlock, Janis; Schatten, Heather T.; Ammerman, Brooke; Andover, Margaret S.; Lloyd-Richardson, Elizabeth E.
Summary: Media coverage of non-suicidal self-injury (NSSI) ranges from providing helpful education to displaying graphic images. We offer the first research-informed, consensus-based guidelines for the responsible reporting and depicting of NSSI in the media, while also advising on ideas for dissemination and collaboration between media professionals and healthcare experts.